Phosphate Binders in CKD: ‟New Kids on the Block” - Afzal, Muhammad Umair; Cheema, Shafeeq (Pakistan Journal of Kidney Diseases, 2021)
Phosphate control is essential component of dietary and medical management of chronic kidney disease (CKD) patients. Hyperphosphatemia has a significant effect on morbidity and mortality of CKD patients. This review takes us through the different older and newer medications available for management of hyperphosphatemia.